Thermal modelling of a dry revolving vane compressor - Aw, Kuan Thai (2018)
The lubricant used in compressors serves to lubricate, to seal the gaps to reduce internal leakage and to a certain extent, to cool. However, a lubricant free compressor is attractive if lubricants become a source of contaminant, or in areas where the compressor needs be placed under any orientation, such as those in military or portable computing. In this paper, a thermal model for a dry revolving vane compressor is presented. This thermal model sets out to predict the steady-state operating temperatures of the compressor components. The lumped thermal conductance method was employed. The results of the components temperature will be presented and discussed. A high potential for overheating is observed at the shaft bearings.